Sticks and Carrots: Two Incentive Mechanisms Supporting Intra-group Cooperation - Janus, Thorsten; Lim, Jamus Jerome (2012)
In this note, we introduce two distinct incentive mechanisms that support dynamic intra-group cooperation in the context of prisoner's dilemma payoffs: rewards for cooperating, and punishments for defection, where the rewarding or punishing party may be outside the relationship.